DOMESTIC TOURISTS’ RESPONSE TO TOURIST ATTRACTIONS IN SABANG AND BANDA ACEH, INDONESIA - Herlina Herlina; Abubakar Hamzah (SCAD Independent, 2015)
This research aimed to determine the response or complaints of domestic tourists about the tourism in Sabang and Banda Aceh. The types of data used were primary and secondary data. The primary data was obtained using Non Probability Sampling method. In-depth interview was conducted with 50 domestic tourists in Sabang and 60 domestic tourists in Banda Aceh. The secondary data was obtained from Statistics Indonesia, Sabang and Banda Aceh Tourism Offices, as well as from relevant literature review. The research revealed that the domestic tourists in Sabang and Banda Aceh had similar responses regarding waste management, environmental hygiene, and adequate lavatories with clean water supply. Another complaint from the domestic tourists in Sabang was regarding transportation such as the ferryboat management and the local ground transportation, availability of restaurants and eateries with wide-ranging types of food, as well as the availability of mushollas or praying spaces. One way to encourage domestic tourists to visit Sabang and Banda Aceh is to address their complaints about waste management and environmental hygiene, availability of restaurants or eateries with a diverse menu, and availability of praying spaces.